Contemporary black women filmmakers and the art of resistance - Baker, Christina N. (Black performance and cultural criticism., 2018)
"An analysis of the films of Black women directors--including Ava DuVernay, Tanya Hamilton, Dee Rees, Kasi Lemmons, and Gina Prince-Bythewood--the book examines how contemporary Black women filmmakers engage in acts of resistance through their filmmaking, using a theoretical lens at the intersection of Black feminism and womanism"--